2007
DOI: 10.1213/01.ane.0000255288.68199.eb
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Stimulation of ST36 (Zusanli) Attenuates Acute Renal but Not Hepatic Injury in Lipopolysaccharide-Stimulated Rats

Abstract: ST36 acupuncture pretreatment significantly attenuated sepsis-induced kidney, but not liver, injury in rats, whereas ST36 acupuncture performed after sepsis induction had no protective effects against sepsis-induced organ injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…27,28 Animal studies have also indicated that acupuncture pretreatment has protective effects against endotoxin-induced acute lung and kidney injuries. 29,30 However, little is known about its biologic basis.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Animal studies have also indicated that acupuncture pretreatment has protective effects against endotoxin-induced acute lung and kidney injuries. 29,30 However, little is known about its biologic basis.…”
Section: Discussionmentioning
confidence: 99%
“…After chronic treatment, liver microsomal lipid peroxidation value decreased significantly. Moreover, given that the manual stimulation of the acupoint ST-36 is able to attenuate renal injury induced by sepsis 10 , it is possible that electrical stimulation of that acupoint can alter the concentrations of MDA, an indicator of cell membrane injury, in renal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…EA is an electrical stimulation through the acupuncture needles with short current pulse at different frequencies [11] . Both EA [10,[21][22][23][24] and MO [25] have been shown to influence renal function, although little is currently understood about their role [26] .…”
mentioning
confidence: 99%